"I enjoy the treadmill very much": Moving beyond traditional understandings of self-efficacy in anti-obesity interventions. (2nd April 2020) - Groven, Karen Synne; Dahl-Michelsen, Tone
ABSTRACT: The last decade has seen increased focus on self-efficacy approaches in anti-obesity interventions. Self-efficacy approaches stemming from Bandura's social cognitive theory involve enhancing the patient's self-efficacy to ensure behavior change through exercise and dietary changes as well as weight-loss control. Inspired by Barad's theory of agential realism, this study explores self-efficacy by acknowledging that also non-human entities have agency. Drawing on one adolescent's experiences of testing herself while running on a treadmill, we put Barad's concept of "intra-acting" into play. Acknowledging the treadmill's agency as well as the agency of the program itself enables us to see the becoming nature of self-efficacy. As such, reading Bandura's concept of self-efficacy through Barad helps us discover more clearly the contingent and fluid process of self-efficacy, a process of becoming that needs to account for both human and non-human actors. Regarding how adolescents' anti-obesity programs can be designed and implemented to enhance self-efficacy, we argue that physiotherapists must understand the intra-active processes involved in such programs.